2023
DOI: 10.1021/acs.jmedchem.2c02123
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of the First Subnanomolar PPARα/δ Dual Agonist for the Treatment of Cholestatic Liver Diseases

Abstract: Peroxisome proliferator-activator receptors α/δ (PPARα/δ) are considered as potential drug targets for cholestatic liver diseases (CLD) via ameliorating hepatic cholestasis, inflammation, and fibrosis. In this work, we developed a series of hydantoin derivatives as potent PPARα/δ dual agonists. Representative compound V1 exhibited PPARα/δ dual agonistic activity at the subnanomolar level (PPARα EC50 = 0.7 nM; PPARδ EC50 = 0.4 nM) and showed excellent selectivity over other related nuclear receptors. The crysta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…After successfully establishing the application of our method, we focused on investigating the synthetic application of the present methodology in the synthesis of biologically valuable targets. Peroxisome proliferator-activated receptor (PPAR) has been a focus of our group’s interest . In 2021, Erhardt and co-workers reported that optimized compound 12 , as a PPAR agonist, exhibited promising potential in treating osteoporosis in mammals .…”
Section: Resultsmentioning
confidence: 99%
“…After successfully establishing the application of our method, we focused on investigating the synthetic application of the present methodology in the synthesis of biologically valuable targets. Peroxisome proliferator-activated receptor (PPAR) has been a focus of our group’s interest . In 2021, Erhardt and co-workers reported that optimized compound 12 , as a PPAR agonist, exhibited promising potential in treating osteoporosis in mammals .…”
Section: Resultsmentioning
confidence: 99%
“…Cholestatic liver disease (CLD) is due to cholestasis caused by gallstones, parasites, etc., resulting in the accumulation of bile acid in the liver and systemic circulation. 1 During the occurrence and development of CLD, the gradual accumulation of bile acid leads to liver damage, inflammation, and fibrosis, and even develops into end-stage liver diseases such as cirrhosis and liver cancer. 2 , 3 Globally, liver cirrhosis is still a major threat to health; there is a 74.53% increase in the number of liver cirrhosis patients from 1990 to 2017.…”
Section: Introductionmentioning
confidence: 99%